2017
DOI: 10.1038/s41598-017-10391-1
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the metabolic mechanism of Diterpene Ginkgolides on antidepressant effects for attenuating behavioural deficits compared with venlafaxine

Abstract: Depression is a severe and chronic mental disorder, affecting about 322 million individuals worldwide. A recent study showed that diterpene ginkgolides (DG) have antidepressant-like effects on baseline behaviours in mice. Here, we examined the effects of DG and venlafaxine (VLX) in a chronic social defeat stress model of depression. Both DG and VLX attenuated stress-induced social deficits, despair behaviour and exploratory behaviour. To elucidate the metabolic changes underlying the antidepressive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Ginkgolides A, B, C were primarily terpenoids and were found that more pharmacological effects improved depression, ischemic stroke and lung injury [18,[49][50][51]. Our earlier experiments demonstrated that ginkgolide C could suppress lipogenesis in 3T3-L1 adipocytes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgolides A, B, C were primarily terpenoids and were found that more pharmacological effects improved depression, ischemic stroke and lung injury [18,[49][50][51]. Our earlier experiments demonstrated that ginkgolide C could suppress lipogenesis in 3T3-L1 adipocytes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that DG ameliorated brain neurotransmitter perturbation and metabolic dysfunction in mice. [8][9][10] However, the underlying molecular mechanisms, including gene-protein-metabolite interactions, remained unclear. Here, we used metabolomics combined with molecular biology methods to explore the antidepressant mechanisms of DG in the HP and PFC.…”
Section: Discussionmentioning
confidence: 99%
“…DG Meglumine Injection was a commercial drug of diterpene ginkgolides, 9,10 which was provided by Jiangsu Kanion Pharmaceutical Co., Ltd (Shanghai, China). It is a mixture of different diterpene ginkgolides (mainly contains ginkgolide A, B and K), which are responsible for the main pharmacological neuroprotective in ginkgo biloba extract.…”
Section: Reagents and Experimental Groupingsmentioning
confidence: 99%
See 2 more Smart Citations